Legal Assistance for the Poor in Rokan Hulu District of Riau Province - Nofrizal Nofrizal (The Indonesian Journal of International Clinical Legal Education, 2019)
The emergence of Law No. 16 of 2011 on legal aid is expected to realize the right society in obtaining justice. Empirically, it is known that the law is enjoyed by many people who has the ability to pay a lawyer or advocate only. While the poor or who are not able to tend to resign with the circumstances, so that the term appears that we often hear, the blunt law upward, sharp down. In Rokan Hulu district of Riau Province the district government together with the DPRD welcomed The law immediately drew up local regulations on legal aid for the poor. It is stated in the rules of the Regional Regulation Rokan Hulu No. 6 on legal aid for the poor, but which became constraint is that in the area still minimal LBH (Legal Aid Institutions) are eligible to give advocacy for the poor in accordance with the requirements requested by the government, the Legal Aid Institute who has been accredited by the Ministry of Law and Human Rights, and accredited by the Ministry of Justice and Human Rights many conditions must be met so that when there is a credible Legal Aid Institution in the area want provide legal assistance to the poor, but cannot be done because of being knocked by requirements required by the government. The hope is that the aspirations of our country in realizing the rights of society in obtaining this justice can be achieved, it needs further arrangements that lead to it the implementation of legal aid programs for these poor communities by taking into account the quantity of legal institutions there are and many conflicts that need to be given advocacy assistance for these incapable people.